Threshold concept learning: Emotions and liminal space transitions. Issue 3 (July 2019) - Irving, Gemma; Wright, April; Hibbert, Paul
This article explores how learners transition through the liminal space when they engage with and master threshold concepts. We investigate this question through a qualitative study of undergraduate students as they grapple with the threshold concept of evidence-based management (EBMgT) as a disciplinary way of thinking and practising. Our findings elaborate threshold concept learning as a cumulative process of the learner's engagement with the troublesome, integrative-and-bounded, irreversible, and transformative elements of a threshold concept. Through this elaboration, we show how transitions through liminal spaces in threshold concept learning play out as an interrelated, cognitive, and affective process. We identify key transition points and mechanisms related to doubt, high-activation negative emotions, regret, and emotional resolution that trigger entry into, progression through or getting stuck within, and exit from a liminal space when a learner engages with and masters a threshold concept. Our research, therefore, contributes processual insight into liminality in threshold concept learning by opening up the transitions and emotions that play out for the learners in the liminal space. We also contribute to wider debates about student engagement with disciplinary ways of thinking and practising in management.